IDENTIFICATIONOF GENERATION Z LEARNING BEHAVIOR IN THE CLASSROOM - Septian, Nandang
One of the important elements on learning process ineducational institution is the classroom. It has hugerole in the user's learning performance. Itsconditionshould be optimized. So far, the procurement ofclassroomshavetended to be focused ondaily maintenance. Meanwhile, the improvementof classroom based on user's preferencestend to be more considered.This phenomenon is based on condition of the current classroom. They were built in the 1970 -1990 period and referred to previous generation preferences. So, they are less relevant for Generation Z student. Theirlearning behavioris different from the previous generations. For example, Generation Z is known to be moreadept at utilizing technology and being all-digital. They also prefer it to be part of learning activities.Based on this phenomenon, research was conducted to identify Generation Z learning behavior. It also tried to find out of the differentbehaviorfrom previous generations. Identification results couldgenerate some dominant factors. They can be used asreferencesfordesigning a classroom that suits Generation Z. As a first step, this study will attempt to explore and understand Generation Z learning behavior as the basis for classroom development. The study result is a description of Generation Z learning behavior. It is expected to be a guide for the development of ideal classroom. Also, the results could become a knowledge related to classroom criteria in digital era.This research usedquantitative method with exploratory factor analysis (EFA). It is used to identify influencing factors on Generation Z learning behavior. Factorsor dimensionsfrom previous studies were elaborated as the sources to arrange instrument test. Resultsof the collected data were analyzed by JASP statistical software using the EFA method. Due to the analysis process, the reduction of factors or dimensions that amounted fromforty was generated into seven new factors. Furthermore, each new factor was labeled, studied in-depth, and the discussion was presented in a descriptive. Those findings are self-impetus, facilitating support, teacher personality, physical environment, self-skill, companionship, and learning material.The seven factors have been sorted based on their influence on Generation Z learning behavior in classroom.Yet, each variablehas correlation and contribution ivwith their respective share. Through the result, the identified factors can be used assourcesfordeveloping suitable educational facilities for Generation Z students. Principals and designers can improve the quality of learning process in classroom